DAMPAK ENVIROMENTAL CONCERN, ADVERTISEMENT DAN ELECTRONIC WORD OF MOUTH PADA GREEN PURCHASE BEHAVIOR - Ming Ming Lukiarti (Jurnal Manajemen dan Profesional, 2021)
The movement to save the environment is increasingly widespread when it is known that the earth's temperature is increasing along with global warming which is difficult to stop. Consumers are increasingly aware of the importance of caring for the environment by buying green products and services, in addition to caring for the surrounding environment as well as to maintain a healthy body. For example, hand-drawn batik with natural dyes, cloth sanitary napkins, clody (baby diapers), plastic that can be recycled and is easily biodegradable, agricultural products and organic cosmetics and other green products (Lukiarti, 2019). This study discusses the impact of three independent variables, namely environmental concern, advertisement and electronic word of mouth on the dependent variable, namely green purchase behavior. The objects in this study are consumers of green products in Indonesia. This study uses the SPSS analysis tool, by calculating the relationship of the independent variables partially and simultaneously to the dependent variable and calculating the weight of the influence of the independent variable on the dependent variable with a determination test. From the results of the reliability and validity test, it is known that the statements on the questionnaire are reliable and valid. The partial test results state that environmental concerns, advertisements and E-WOM partially have a positive and significant impact on green purchase behavior. Simultaneous test results show that environmental concerns, advertisements and E-WOM simultaneously have a positive and significant impact on green purchase behavior.